If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 4x = 3x + -8 Reorder the terms: 3 + 4x = -8 + 3x Solving 3 + 4x = -8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + 4x + -3x = -8 + 3x + -3x Combine like terms: 4x + -3x = 1x 3 + 1x = -8 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + 1x = -8 + 0 3 + 1x = -8 Add '-3' to each side of the equation. 3 + -3 + 1x = -8 + -3 Combine like terms: 3 + -3 = 0 0 + 1x = -8 + -3 1x = -8 + -3 Combine like terms: -8 + -3 = -11 1x = -11 Divide each side by '1'. x = -11 Simplifying x = -11
| 21+1.5x=28-2x | | 5t+9+2t=11+5t | | -4(y-2y)+7=-4(5y-y)+4+19y | | x^2-x+x=-1+1-1 | | 2k+3=14 | | -3(x-2)=6x+2 | | 6a+9-4a=13-2a | | 82-5x=7 | | 40x^2-182x+51=0 | | -5+3c=-14 | | 6=x/6+7 | | x(x+5)=12 | | 9-7t=49+t | | 6x+39=14-41 | | x(x+1)=200 | | (3x+5)(8)= | | 8x=168 | | 6(2n+9)=114 | | 7(9x-8)= | | 8x-18=150 | | 2n-9+5n=6+4n | | -4+v/9=2 | | 8x+4y= -56 | | -6y-5=13 | | 6a+12=66 | | 3x+y= -12 | | 6x-7=331 | | 4(2x+4)-2(x-2)=4(x-2) | | 2x^2+288=0 | | 6n+2(4n+5)= | | y=x^2+15x+56 | | X*6+80=X*13+11 |